THE DURATION OF GADGET USE WITH THE DEVELOPMENT OF SOCIAL INTERACTION IN CHILDREN AT SDN 1 CRAKEN - Intan Fazrin; Intan Fuji Lestari (Universitas Karya Husada Semarang, 2024)
Gadgets can be found anywhere, both adults and children. Children have now become active consumers where many electronic products and gadgets make children their target market. Apart from children, parents also love gadgets so much that they are called gadget crazy. The purpose of this research is to analyze the relationship between the duration of gadget use and the development of social interaction in children at SDN 1 Craken. The design of this research is quantitative observational research with a cross-sectional approach with the research focus directed at analyzing the relationship between the duration of gadget use and the development of social interaction in children at SDN 1 Craken. The total population was 33 respondents, the sample was 30 respondents taken using the Simple Random Sampling technique. The research results showed that the majority of respondents who used gadgets lasted 1-2 hours, namely 12 respondents (40.0%). Most of the respondents had sufficient development in the social interaction category, namely 14 respondents (46.7%). Based on the results of the Spearmen Rank analysis, it shows that the p-value is 0.000 < 0.05, so H1 is accepted so it can be concluded that there is a partial relationship between the duration of gadget use and the development of social interaction in students. children at SDN 1 Craken. It is hoped that parents will pay attention to how gadgets affect children's social interactions. Apart from that, it also records in detail the social activities carried out by children outside of gadget use to obtain a more comprehensive picture of the relationship between the duration of gadget use and the development of their social interactions.